Modular metal-free catalytic radical annulation of cyclic diaryliodoniums to access π-extended arenes. Issue 5 (22nd February 2021) - Zhu, Daqian; Peng, Hui; Sun, Yameng; Wu, Zhouming; Wang, Yun; Luo, Bingling; Yu, Tiantian; Hu, Yumin; Huang, Peng; Wen, Shijun
Abstract : Tert -butylamine-catalyzed free radical annulations with cyclic diaryliodoniums occur in environmentally friendly ethyl acetate and do not require transition metal, providing diversified polycyclic aromatic hydrocarbons by modulating substituents. Abstract : Polycyclic aromatic hydrocarbons (PAHs) are of increasing importance in the advanced material field. Cyclic diaryliodonium salts are non-toxic and environmentally benign arylating reagents. Here, we describe an alkylamine-mediated free radical intramolecular annulation to access PAHs under environmentally friendly conditions. On modulating substituents and their positions in the iodoniums, the free radical reaction controllably underwent three types of cyclization including ring contraction and ring switch to form tricyclic and tetracyclic frameworks of PAHs. Preliminary mechanistic studies implied that alkylamines initiated a radical pathway to complete the cyclization efficiently. Moreover, these acquired products were further converted into diverse complex graphene segments.